The Effectiveness of the Coretax System as a Support for the Quality of Tax Services at the Kediri Pratama Tax Service Office (KPP) - Kharisma Rada Ikrima Salsabila; Dwi Ari Pertiwi (Universitas Muhammadiyah Ponorogo, 2025)
Digital transformation in tax administration plays a crucial role in improving service effectiveness and the quality of public services. This study aims to analyze the effectiveness of the Coretax System in supporting the quality of tax services at the Pratama Tax Office (KPP) Kediri. This research employed a qualitative descriptive approach with data collected through in-depth interviews, direct observation, and documentation involving tax officers and taxpayers who used the Coretax System during the period of September to November 2025. The results indicate that the Coretax System contributes significantly to faster service processes, improved accuracy and integration of information, easier access for taxpayers, and higher efficiency in administrative procedures. Nevertheless, several challenges were identified, including system slowdowns during peak service hours, incomplete data migration, and limited digital literacy among some taxpayers. Overall, the Coretax System is considered effective in enhancing tax service quality at KPP Pratama Kediri, although further optimization is still required to improve system stability and strengthen user readiness.